Implementation of Corporate Social Responsibility (CSR) and Community Response around the Company PT. Bumi Sari Prima Pematang Siantar in the Perspective of Islamic Business Ethics - Lidya Asterina; Mustafa Kamal Rokan; Marliyah Marliyah (Jurnal Ilmiah Mizani: Wacana Hukum, Ekonomi Dan Keagamaan, 2022)
This study aims to deeply analyze about: 1) PT. Bumi Sari Prima Pematang Siantar, 2) Implementation of PT. Bumi Sari Prima Pematang Siantar to the Community and the Response of the community around the PT. Bumi Sari Prima Pematang Siantar, and 3) Shariah Enterprise Theory (SET) Review of PT. Bumi Sari Prima Pematang Siantar. This research is a field research with a descriptiveinductive type of qualitative research. The subjects of this study were the community and employees of PT. Bumi Sari Prima Pematang Siantar. The results showed that PT. Bumi Sari Prima Pematang Siantar is carried out in the form of (1) Giving Cash to the surrounding community, (2) Handing over assets / grants to be used, (3) Providing the company's products to the community every year, (3) Providing Free Services to people who have interests, (4) Allowing the use of company facilities for community activities, (5) Recruiting workers in the surrounding environment (6) providing social assistance, (7) Management and Protection of the environment, (8) Human Resource Development. Implementation of PT. Bumi Sari Prima Pematang Siantar was well distributed, and received a positive response from the community around the company for the company's CSR program. Shariah Enterprise Theory review of the implementation of PT. Bumi Sari Prima Pematang Siantar when viewed in terms of objectives, that this program is in accordance with the principle of sharing Adil, Maṣlaḥah and Raḥmatan lil‟alamῑn